STUDY ON NUTRITION OF EGGS JELAWAT (Leptobarbus hoeveni Blkr) - Aryani, Netti; Zen, Zuhelmi; Syandri, Hafrijal; Jaswandi, Jaswandi (Jurnal Perikanan dan Kelautan, 2009)
The purpose of study is to know nutrition of jelawat eggs, compriseprorein, fat, calcium, phospore, essential amino acid, essential fatty acid, vitamineC and vitamine E. Method applied to get the purpose is take jelawat eggshave TKG IV ( gonad stages mature) on brood stock with 4kg, and weight wet ofgonad 600 gram at Maninjau Lake. Eggs are dried and floured. The study usesproximate-analysis to get quantity of protein, fat, calcium and phospore andHPLC methode to get the essential amino acid, fatty acid and vitamine C and E.The result show that fish jelawat floured have within it nutrition protein61,33 %, fat, 11,90 %, water content 4,88 %, ashes content 8,26 %. Quantityamino acid 52,69 %, linoleat fatty acid 7,71.%, linolenat fatty acid 0,05 %,vitamine C 0,240 % and vitamine E 0,310 %.